Respuesta :

genan

Answer:

f(x) = (x + 1)^2 + 2

Step-by-step explanation:

A parabola function has different forms:

standard form: f(x) = ax + bx + c^2

vertex form:  f(x) = a (x − h)^2 + k

Our equation that includes a horizontal translation is h

- negative h shifts right

- positive h shifts left

this graph shows a shift to the left by 1 so h = 1

Our equation that includes a vertical translation is k

- negative k shifts down

- positive k shifts up

this graph shows a shift to the up by 2 so k = 2

- a represents a compression / stretch which seems not to be in this graph

combine, f(x) = (x + 1)^2 + 2

ACCESS MORE